Project Management / A Managerial Approach: Ninth Edition - Mantel Samuel J; Meredith Jack R; Shafer Scott M (Wiley, 2016)
This collaborative learning environment provides immediate insight into strengths and problem areas through a combination of dynamic course materials and visual reports so that both you and your students can act on what's most important. Projects in Contemporary Organizations, Project Initiation, Strategic Management and Project Selection, The Project Manager, Managing Conflict and the Art of Negotiation, The Project in the Organizational Structure, Project Planning, Project Activity and Risk Planning, Budgeting: Estimating Costs and Risks, Scheduling, Resource Allocation, Project Execution, Monitoring and Information Systems, Project Control, Project Auditing, Project Termination, Appendices, Author and Subject Index.